Therapeutic Management of Babesiosis in a Cow: A Case Report - Bante, Shivani; Bagherwal, Rajendra Kumar; Agrawal, Vivek; Rajoriya, Shweta (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Babesiosis is a haemoprotozoan disease intraerythrocytic protozoan parasites of the genus Babesia that infect a wide range of domestic and wild animals. It is one of the common tick borne haemoprotozoan diseases affecting the bovines in tropical and subtropical parts of Africa, Australia, America, and Asia including India (Kumar and Kala, 2018). In India, annual economic losses to livestock due to babesiosis are estimated to be about 57.2 million US dollars which is mainly caused by two most important species, i.e., Babesia bovis and Babesia bigemina (Bock et al., 2004). The cattle tick Rhipicephalus microplus is the main vector involved with the transmission and is the only known vector for bovine babesiosis (Souza et al., 2018). Due to universal distribution of the ixodid tick, babesiosis is considered as the second most widespread blood-borne disease of animals (Homer et al., 2000) and is prominently gaining increasing interest as an emerging zoonosis of humans also (Homer et al., 2000; Zintl et al., 2003). Clinical symptoms of Babesiosis are classical haemoglobinuria which is often present, with anaemia and jaundice that develops especially in more protracted cases (Bock et al., 2004). The disease has been recorded in all the cattle breeds but more commonly in exotic and crossbred cattle than in indigenous ones (Chakrabarti, 2003). The present communication describes the haemato-biochemical profile and therapeutic management of a non-descript native cow with babesiosis infection.